Influence of paraoxonase-1 Q192R and cytochrome P450 2C19 polymorphisms on clopidogrel response - Li L (Dove Medical Press, 2012)
Rolf P Kreutz1,2, Perry Nystrom2, Yvonne Kreutz2, Jia Miao2, Zeruesenay Desta2, Jeffrey A Breall1, Lang Li2, ChienWei Chiang2, Richard Kovacs1, David A Flockhart2, Yan Jin21Krannert Institute of Cardiology, 2Division of Clinical Pharmacology, Indiana University School of Medicine, Indianapolis, IN, USABackground: The metabolic activation of clopidogrel is a two-step process. It has been suggested that paraoxonase-1 (PON1) is a rate-limiting enzyme in the conversion of 2-oxo-clopidogrel to an active thiol metabolite. Conflicting results have been reported in regard to (1) the association of a common polymorphism of PON1 (Q192R) with reduced rates of coronary stent thrombosis in patients taking clopidogrel and (2) its effects on platelet inhibition in patient populations of European descent. Methods: Blood samples from 151 subjects of mixed racial background with established coronary artery disease and who received clopidogrel were analyzed. Platelet aggregation was determined with light transmittance aggregometry and VerifyNow® P2Y12 assay. Genotyping for cytochrome P450 2C19 (CYP2C19)*2 and *3 and PON1 (Q192R) polymorphisms was performed.Results: Carriers of CYP2C19*2 alleles exhibited lower levels of platelet inhibition and higher on-treatment platelet aggregation than noncarriers. There was no significant difference in platelet aggregation among PON1 Q192R genotypes. Homozygous carriers of the wild-type variant of PON1 (QQ192) had similar on-treatment platelet reactivity to carriers of increased-function variant alleles during maintenance clopidogrel dosing, as well as after administration of a clopidogrel 600 mg loading dose.Conclusion: CYP2C19*2 allele is associated with impaired platelet inhibition by clopidogrel and high on-treatment platelet aggregation. PON1 (Q192R) polymorphism does not appear to be a significant determinant of clopidogrel response.Keywords: PON1, platelet, aggregation, cytochrome P450 enzymes